Dermatological Manifestations and Sebum Composition in Parkinson’s Disease - Paz, Meshi; Lio, Peter (Dermatology Practical & Conceptual, 2025)
Introduction Parkinson disease (PD) is a multifaceted neurodegenerative disorder known for its hallmark motor symptoms. However, nonmotor manifestations, specifically dermatological changes, precede motor symptoms and may thus serve as vital early indicators of PD. Objectives This article explores the skin-related changes associated with PD, focusing on alterations in sebum composition, microbial dysbiosis, and the potential for leveraging dermatological assessments as early, noninvasive diagnostic markers for PD. Methods A comprehensive literature review was conducted to investigate dermatological manifestations of PD, focusing on sebum changes in affected individuals. Research explored the clinical relevance of altered lipid profiles, volatile organic compound (VOC) contributions, and microbiome dysbiosis in those with PD. Results Individuals with PD exhibit excess sebum production characterized by altered lipid profiles, including elevated short-chain fatty acids (SCFAs) and disruptions in sphingolipid metabolism. The lipid-rich environment also promotes overgrowth of Malessezia yeast, contributing to varied dermatological symptoms in those with PD. VOCs identified in sebum have been linked to unique odors and serve as biomarkers for diagnostic potential. These findings support the potential for early PD diagnosis through dermatologic assessment and sebum analysis. Conclusion Dermatological manifestations in PD offer promising noninvasive biomarkers for early diagnosis. Future research should aim to further elucidate the mechanisms underlying sebum dysregulation in PD and validate the clinical relevance of these biomarkers in larger populations.